Quantification of Pseudomonas aeruginosa in multispecies biofilms using PMA-qPCR - Sarah Tavernier; Tom Coenye (PeerJ, 2015)
Multispecies biofilms are an important healthcare problem and may lead to persistent infections. These infections are difficult to treat, as cells in a biofilm are highly resistant to antimicrobial agents. While increasingly being recognized as important, the properties of multispecies biofilms remain poorly studied. In order to do so, the quantification of the individual species is needed. The current cultivation-based approaches can lead to an underestimation of the actual cell number and are time-consuming. In the present study we set up a culture-independent approach based on propidium monoazide qPCR (PMA-qPCR) to quantify Pseudomonas aeruginosa in a multispecies biofilm. As a proof of concept, we explored the influence of the combined presence of Staphylococcus aureus, Streptococcus anginosus and Burkholderia cenocepacia on the antimicrobial susceptibility of P. aeruginosa using this PMA-qPCR approach.